Divergence of allosteric effects of rapacuronium on binding and function of muscarinic receptors - Jakubík, Jan; Randáková, Alena; El-Fakahany, Esam E; Dolezal, Vladimír (BMC pharmacology, 2009)
BACKGROUND: Many neuromuscular blockers act as negative allosteric modulators of muscarinic acetylcholine receptors by decreasing affinity and potency of acetylcholine. The neuromuscular blocker rapacuronium has been shown to have facilitatory effects at muscarinic receptors leading to bronchospasm. We examined the influence of rapacuronium on acetylcholine (ACh) binding to and activation of individual subtypes of muscarinic receptors expressed in Chinese hamster ovary cells to determine its receptor selectivity. RESULTS: At equilibrium rapacuronium bound to all subtypes of muscarinic receptors with micromolar affinity (2.7-17 microM) and displayed negative cooperativity with both high- and low-affinity ACh binding states. Rapacuronium accelerated [3H]ACh association with and dissociation from odd-numbered receptor subtypes. With respect to [35S]GTPgammaS binding rapacuronium alone behaved as an inverse agonist at all subtypes. Rapacuronium concentration-dependently decreased the potency of ACh-induced [35S]GTPgammaS binding at M2 and M4 receptors. In contrast, 0.1 microM rapacuronium significantly increased ACh potency at M1, M3, and M5 receptors. Kinetic measurements at M3 receptors showed acceleration of the rate of ACh-induced [35S]GTPgammaS binding by rapacuronium. CONCLUSIONS: Our data demonstrate a novel dichotomy in rapacuronium effects at odd-numbered muscarinic receptors. Rapacuronium accelerates the rate of ACh binding but decreases its affinity under equilibrium conditions. This results in potentiation of receptor activation at low concentrations of rapacuronium (1 microM) but not at high concentrations (10 microM). These observations highlight the relevance and necessity of performing physiological tests under non-equilibrium conditions in evaluating the functional effects of allosteric modulators at muscarinic receptors. They also provide molecular basis for potentiating M3 receptor-mediated bronchoconstriction.
Keywords: Receptors, Muscarinic; kompetitivní vazba; Guanosine 5'-O-(3-Thiotriphosphate); CHO buňky; Radioligand Assay; Animals; agonisté muskarinových receptorů; acetylcholin; Neuromuscular Nondepolarizing Agents; Muscarinic Agonists; N-Methylscopolamine; alosterická regulace; radioligandová zkouška; Vecuronium Bromide; N-methylskopolamin; Female; nedepolarizující myorelaxancia; Acetylcholine; Cricetulus; Binding, Competitive; alosterické místo; křečci praví; ženské pohlaví; Cricetinae; Allosteric Site; CHO Cells; zvířata; vekuronium; receptory muskarinové; Allosteric Regulation; guanosin 5'-O-(3-thiotrifosfát)